2015
DOI: 10.1016/j.alcohol.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

The reinforcing properties of ethanol are quantitatively enhanced in adulthood by peri-adolescent ethanol, but not saccharin, consumption in female alcohol-preferring (P) rats

Abstract: Alcohol drinking during adolescence is associated in adulthood with heavier alcohol drinking and an increased rate of alcohol dependence. Past research in our laboratory has indicated that peri-adolescent ethanol consumption can enhance the acquisition and reduce the rate of extinction of ethanol self-administration in adulthood. Caveats of the past research include reinforcer specificity, increased oral consumption during peri-adolescence, and a lack of quantitative assessment of the reinforcing properties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…Alcohol consumption in rodents is known to vary by species, strain, method, and environment (Crabbe et al., ; Fritz and Boehm, ). Nevertheless, the majority of rodent studies, including those from the NADIA Consortium, report that AIE often, although not always (Moaddab et al., ; Nentwig et al., ; Toalston et al., ; Varlinskaya et al., ), promotes adult alcohol drinking in multiple rat strains (Alaux‐Cantin et al., ; Broadwater et al., ; Gass et al., ; Lee et al., ; Pandey et al., ; Pascual et al., ; Rodd‐Henricks et al., ; Toalston et al., ; Wille‐Bille et al., ). These studies use a variety of AIE exposures as well as alcohol consumption paradigms.…”
Section: Persistent Aie‐induced Effects On Behaviormentioning
confidence: 99%
“…Alcohol consumption in rodents is known to vary by species, strain, method, and environment (Crabbe et al., ; Fritz and Boehm, ). Nevertheless, the majority of rodent studies, including those from the NADIA Consortium, report that AIE often, although not always (Moaddab et al., ; Nentwig et al., ; Toalston et al., ; Varlinskaya et al., ), promotes adult alcohol drinking in multiple rat strains (Alaux‐Cantin et al., ; Broadwater et al., ; Gass et al., ; Lee et al., ; Pandey et al., ; Pascual et al., ; Rodd‐Henricks et al., ; Toalston et al., ; Wille‐Bille et al., ). These studies use a variety of AIE exposures as well as alcohol consumption paradigms.…”
Section: Persistent Aie‐induced Effects On Behaviormentioning
confidence: 99%
“…Studies using animal models have also indicated that voluntary ethanol drinking during adolescence can, in some models, be shown to facilitate the acquisition of alcohol self-administration, increase craving behavior, and/or increase the probability of relapse in those animals in adulthood (see Alaux-Cantin et al, 2013; Gilpin, Karanikas & Richardson, 2012; Jeanblanc et al, 2015; McBride et al, 2005; Serlin & Torregrossa, 2015; Spear, 2000a; Toalston et al, 2015). However, other studies have shown that ethanol exposure during adolescence has no effect on subsequent ethanol consumption in adulthood (Slawecki & Betancourt, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the causal ambiguity in human studies, longitudinal preclinical studies allow scientists to isolate the effects of adolescent alcohol exposure on behavior and neurobiology in adulthood (Crews et al., ). To date, such studies have shown that adolescent intermittent ethanol (AIE) exposure leads to impaired reversal learning (Coleman et al., ), enhanced cue‐driven behavior (McClory and Spear, ), increased ethanol (EtOH)‐induced conditioned place preference (Pascual et al., ), greater EtOH self‐administration (Pascual et al., ; Toalston et al., ; but see Slawecki and Betancourt, ), and resistance to extinction of EtOH self‐administration (Gass et al., ; Toalston et al., ).…”
mentioning
confidence: 99%